Obesity, Weight Loss, and Employment Prospects – Evidence from a Randomized Trial - Arndt R. Reichert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This study presents credible estimates for the causal effect of a variation in obesity on employment. By exploring random assignment of a weight loss intervention based on monetary rewards, I provide convincing evidence that weight loss positively affects the employment prospects of obese women but not of obese men. Consistent with this, significant effects of weight loss on proxy variables for labor productivity are found only for obese women. – – Die vorliegende Studie behandelt den kausalen Effekt von individueller Fettleibigkeit auf die Beschäftigungswahrscheinlichkeit. Die empirische Analyse nutzt die mittels eines zufällig zugewiesenen (randomisierten) finanziellen Anreizsystems erzeugte Variation im Körpergewicht zur Schätzung des Wirkungszusammenhangs. Zentrales Ergebnis ist, dass bei fettleibigen Frauen die Reduktion des Köpergewichts eine Verbesserung der Beschäftigungschancen bewirkt, bei fettleibigen Männern hingegen nicht. Konsistent damit können weiter reichende Analysen lediglich bei fettleibigen Frauen Effekte auf Proxyvariablen für die Arbeitsproduktivität nachweisen.
Keywords: I10; I18; J24; J21; 330; obesity; weight loss intervention; IV estimation; sample selection; labor productivity; employment